Investigation on the interactions among lignocellulosic constituents and minerals of biomass and their influences on co-firing - Shi, Kaiqi; Oladejo, Jumoke Mojisola; Yan, Jiefeng; Wu, Tao (Elsevier, 2019)
The influences of biomass constituents, such as lignocellulosic components and minerals, on the combustion of coal/biomass blends are of significant importance in co-firing due to its potential impacts on ignition, flame stability and burnout. In this research, combustion characteristics of pure lignocellulosic elements, Rosewood, Mengxi coal and their blends were studied in detail. The effect of minerals in Rosewood on combustion of biomass/Mengxi coal blends was investigated which revealed reductions in the ignition (≤20 °C), peak (≤12 °C)and burnout temperatures (≤6 °C). The results also demonstrate the existence of interactions between lignocellulosic constituents in the model biomass, which is dominated by the interactions of cellulose-derived products with xylan and lignin respectively which led to ∼8% reduction in char oxidation temperature. The minerals in biomass showed different impacts at different stages of the combustion process, such as inhibition effect during the devolatilization stage, and promotive synergy (mainly due to calcium)on ignition and char oxidation. © 2019 Elsevier Ltd